Implementation of Islamic Marketing Ethics at Bank Mega Syariah Sub-Branch Office (KCP) Palembang - Listiawati; Muhammad Faris Afif; Zikri Rahmani; Tazhirowati (CV. Era Digital Nusantara, 2025)
This study aims to analyze the implementation of Islamic marketing ethics at Bank Mega Syariah Sub-Branch Office (KCP) Palembang. Islamic marketing ethics refer to principles derived from Islamic teachings in marketing activities, emphasizing honesty, fairness, responsibility, and the absence of fraud or exploitation. This research employs a qualitative descriptive approach. Data were collected through in-depth interviews with management and marketing staff, direct observation, and documentation. The findings indicate that Bank Mega Syariah KCP Palembang has consistently applied the principles of Islamic marketing ethics, particularly in terms of honest product information, transparency in contracts (akad), fair service to customers, and avoiding excessive promotional practices. However, some challenges remain, such as limited understanding among certain marketing personnel regarding Islamic principles and the pressure to meet business targets. Therefore, enhanced internal training based on Islamic values is necessary to strengthen commitment and improve service quality in accordance with sharia principles.